Design, Synthesis, Molecular Docking And Cytotoxic Activity Of New Ortho-Hydroxy Chalcone And Pyrazoline Derivatives - Luhaibi, Maadh Jumaah Owaid (2019)
This study focused on the design and synthesis of new compounds with anticancer activity. The compounds were constructed using the structure-based drug design, focusing on their binding capabilities to the Colchicine (PDB code: IS AO) active site in a bidentate manner, with the most energetically preferable binding modes using Autodock Vina 1.1.2 and Discovery studio 4.1. In the molecular docking analysis, the binding energy and interactions between protein receptors and ligands provide a better understanding of the biological functions to determine the amino acid residues which are crucial to docking interactions. The modification and replacement of the pyrazoline structure and chaicone led to the development of the structureactivity relationship and identified potent and selective inhibitors of drug design.